PENGARUH IKLAN DAN PERSONAL SELLING PRODUK SUSU PRENAGEN TERHADAP MINAT BELI SUSU PRENAGEN HAMIL (STUDI KASUS KONSUMEN DI RSIA YK MADIRA PALEMBANG) - M.A. Baidowi; Rudi Chairudin (JURNAL KOMPETITIF, 2022)
The purpose of this study was to analyze the effect of advertising and personal selling on consumers' buying interest in prenagen milk (pregnant). The data used were sourced from buyers of prenagen milk products at RSIA YK Madira Palembang with a sample of 40 people. Analysis of the data used to determine the effect either simultaneously or partially is to use multiple linear regression analysis. From the results of simultaneous research analysis that advertising and personal selling have an effect on buying interest in prenagen milk, this can be seen from the results of the F test which has a significance of 0.000. and partially the advertising variable has a significant effect of 0.000, with a regression coefficient of 0.583 on buying interest while the personal selling variable has a significant effect on 0.001 on buying interest with a regression coefficient of 0.306 and both show a significant level below 0.05. Furthermore, seen from the coefficient of determination or R square of 0.932, which means that 93% of buying interest is influenced by advertising and personal selling and the remaining 6.8% or 7% is influenced by other factors not examined in this study. Keywords: Advertising; Personal Selling; Buying Interest